2016
DOI: 10.19044/esj.2016.v12n10p340
|View full text |Cite
|
Sign up to set email alerts
|

Youth Employment in Rural Albania: A Theoretical Approach

Abstract: Employment plays a central role in the social integration of young people. Young people in rural areas are the future of agriculture and other rural industries, but often lack the guidance and support necessary to fully contribute to the development of their communities, thereby fuelling the vicious cycle of rural underdevelopment and poverty. This study aims to gain a better understanding of the youth employment challenges faced in rural areas by bringing together in group discussions with stakeholders (farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…However, several factors influence the decision of youths to engage in off-farm employment and to determine the type of jobs they engage in. References [4,[17][18][19] revealed that due to restricted opportunities in rural areas, desperate youths going into off-farm work choose low-paying, unskilled off-farm wage employment to earn a living [4,[18][19][20]. The low employment opportunities for youths in rural areas have been related to the underdevelopment and poor access to economic resources [21].…”
Section: Nigerian Youth Employment and Sustainable Development Policiesmentioning
confidence: 99%
“…However, several factors influence the decision of youths to engage in off-farm employment and to determine the type of jobs they engage in. References [4,[17][18][19] revealed that due to restricted opportunities in rural areas, desperate youths going into off-farm work choose low-paying, unskilled off-farm wage employment to earn a living [4,[18][19][20]. The low employment opportunities for youths in rural areas have been related to the underdevelopment and poor access to economic resources [21].…”
Section: Nigerian Youth Employment and Sustainable Development Policiesmentioning
confidence: 99%
“…They are the single most important part of the data collection. The researcher is trusting their insight and, therefore, choosing the best possible participants is extremely important (Mece, 2016)…”
Section: Attitudes Towards the Focus Group Processmentioning
confidence: 99%